Transdisciplinary Digital Art - Adams, Randy (Springer, 2017)
This volume collects selected papers from the past two instances of Digital Art Weeks (Zurich, Switzerland) and Interactive Futures (Victoria, BC, Canada), two parallel festivals of digital media art. The work represented in Transdisciplinary Digital Art is a confirmation of the vitality and breadth of the digital arts. Collecting essays that broadly encompass the digital arts, Transdisciplinary Digital Art gives a clear overview of the on-going strength of scientific, philosophical, aesthetic and artistic research that makes digital art perhaps the defining medium of the 21st Century.